Going Paperless in Education: A Circular Economy Approach in Cambodian High Schools - Hok, SreyOun; Serey, Mardy; Mom, Ket; Tum, Saravuth; Hem, Suntrakwadh; Hong, Chhun (Room of Civil Society Development, 2025)
This study examines students’ readiness to adopt paperless learning within the Circular Economy framework in senior high schools in Svay Rieng Province, Cambodia. It analyzes the influence of environmental awareness, digital literacy, and habitual behavior on preparedness for transitioning from paper-based to digital learning. A quantitative descriptive approach was applied, using survey data from 148 students. Instrument validity and reliability were confirmed, and multiple regression analysis was conducted to assess the relationships among variables. The results indicate that all three factors significantly influence readiness, with digital literacy as the strongest predictor, followed by habits and environmental awareness. Together, these variables explain 51.3% of the variance in student preparedness. The findings extend existing technology adoption models, including the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), by integrating environmental and behavioral dimensions. Practically, the study emphasizes the need to strengthen digital literacy through training and curriculum integration, supported by programs that foster environmental responsibility and sustainable learning habits. These insights provide a policy framework for schools and policymakers in developing contexts to implement paperless education effectively and inclusively.